Vegetation indices and field spectroradiometric measurements for validation of buried architectural remains: verification under area surveyed with geophysical campaigns - Hadjimitsis, Diofantos G.; Agapiou, Athos (My University, 2011)
This study presents an alternative approach for detecting possible archaeological crop marks using medium multitemporal resolution satellite data and field spectroscopy measurements during a whole phenological cycle of the crops and normalized difference vegetation index (NDVI) values. Geophysical surveys have been carried out on areas where archaeological remains with crops existed for validation and verification. The study presents the results obtained by applying the NDVI for a series of multitemporal Landsat TM/ETM+ images acquired from June 2009 to June 2010, intended for detecting archaeological crop marks in the Paphos District area in Cyprus. The results were validated using in situ spectroradiometric measurements using the GER 1500 field spectroradiometer. The authors compared the NDVI values between three sites in which barley crop is cultivated during a complete phenological cycle. The first site was a known archaeological area (Site 1), while the other two sites were healthy cultivated areas (Sites 2 and 3). The sites had similar soil and climatic characteristics. It has been found that during the phenological cycle, the NDVI plot for Site 1 was significantly different from the healthy areas. The detection of possible archaeological areas was based on anomalies observed and measured on vegetation indices, during the phenological cycle, of the “stressed” barley compared to healthy “nonstressed” barley in all three sites. At the end of the life cycle (after June 2010), the local authorities commenced excavation work at Site 1. Buried archaeological remains, 20 to 30 cm below ground surface were found. Anomalies found in the NDVI phenological cycle, as in Site 1, could be used for detecting areas with buried archeological remains
Keywords: Αrchaeological crop marks; Βuried archaeological remains; Phenological cycle; Spectral signature anomalies; Spectroradiometric measurements